Amorphous carbon layer contributing Li storage capacity to Nb2O5@C nanosheets1. Issue 45 (20th May 2015) - Wang, Lei; Ruan, Boyang; Xu, Jiantie; Liu, Hua Kun; Ma, Jianmin
<x xml:space="preserve">Abstract</x> The high-capacity of Nb2O5 nanosheets has been successfully realized through introducing amorphous carbon layers, which have been demonstrated to have a large capacity owing to the existence of defects on amorphous carbon layers.